Peran hidden curriculum terhadap stres akademik mahasiswa jurusan Sastra Jerman - Rizqi Oktaputriviant, Nidia; Hermilia Wijayati, Primardiana (2020)
This research is a qualitative research study that aims to describe the hidden curriculum of the Department of German Literature, State University of Malang and its function to mitigate students' academic stress. Data for this study was collected through observations and interviews. The results of this study show the hidden curriculum is manifested through attitudes towards learning. Students' independence and responsibility are factors that help students deal with academic stress.